2015
DOI: 10.1177/0363546515570621
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Dislocation Arthropathy

Abstract: At an average 13 years after arthroscopic Bankart repair, osteoarthritic changes are a common finding and, overall, are comparable with reports in the literature regarding open procedures as well as nonoperative treatment. The extent of trauma sustained during preoperative dislocations and the age of the patient seem to be more relevant for long-term dislocation arthropathy than the kind of treatment. Accordingly, the study hypothesis must be rejected. Avoiding preoperative dislocations is more important for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
50
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 41 publications
8
50
1
4
Order By: Relevance
“…Plath and colleagues [19] in a very recent publication, report on the clinical outcome as well as the rate of dislocation arthropathy in a rather large population of instability patients treated arthroscopically and followed for a minimum of 10 years (mean follow-up time: 13 years). They conclude that the overall clinical outcome was satisfactory, reporting a median Constant score of 94 and minimal external rotation deficit as compared to the contralateral shoulder.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Plath and colleagues [19] in a very recent publication, report on the clinical outcome as well as the rate of dislocation arthropathy in a rather large population of instability patients treated arthroscopically and followed for a minimum of 10 years (mean follow-up time: 13 years). They conclude that the overall clinical outcome was satisfactory, reporting a median Constant score of 94 and minimal external rotation deficit as compared to the contralateral shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…No such evidence was available concerning the long term effect of arthroscopic anatomic procedures on the prevalence and evolution of dislocation arthropathy until recently, when a number of publications have demonstrated that the long-term incidence of moderate and severe dislocation arthropathy is similar to that reported following open anatomic procedures [18, 19, 28]. Furthermore, it has been suggested that glenohumeral chondrolysis can occur following arthroscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations